2019
DOI: 10.1016/j.molbiopara.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence staining protocol for STED nanoscopy of Plasmodium-infected red blood cells

Abstract: Immunofluorescence staining is the key technique for visualizing organization of endogenous cellular structures in single cells. Labeling and imaging of blood stage Plasmodium falciparum has always been challenging since it is a small intracellular parasite. The gold standard for parasite immunofluorescence is fixation in suspension with addition of minute amounts of glutaraldehyde to the paraformaldehyde-based solution. While this maintains red blood cell integrity, it has been postulated that antigenicity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 28 publications
13
45
0
Order By: Relevance
“…S5). Our results on asexual parasites recapitulate previous findings obtained by high-resolution microscopy 80,84,85 . These studies showed that merozoites and ring stage parasites possess only three to seven nuclear pores that are closely clustered in one region of the nuclear membrane.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…S5). Our results on asexual parasites recapitulate previous findings obtained by high-resolution microscopy 80,84,85 . These studies showed that merozoites and ring stage parasites possess only three to seven nuclear pores that are closely clustered in one region of the nuclear membrane.…”
Section: Discussionsupporting
confidence: 91%
“…S4). Validation of the NF54/iGP2_NUP313-mSc line by live cell fluorescence imaging verified the expected localization of nuclear pores across the different IDC stages as determined in previous studies 80,84,85 (Fig. 4a).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…S5). Our results on asexual parasites recapitulate previous ndings obtained by highresolution microscopy 80,84,85 . These studies showed that merozoites and ring stage parasites possess only three to seven nuclear pores that are closely clustered in one region of the nuclear membrane.…”
Section: Discussionsupporting
confidence: 90%
“…Validation of the NF54/iGP2_NUP313-mSc line by live cell uorescence imaging veri ed the expected localization of nuclear pores across the different IDC stages as determined in previous studies 80,84,85 ( Fig. 4a).…”
Section: Further Genetic Manipulation Of Igp Parasites For the Targetsupporting
confidence: 81%